PREDICTING HYDROCARBON FIELDS USING THE COMPLEX OF ATMOGEOCHEMICAL AND REMOTE SENSING METHODS - Azimov О.; Bagriy І.; Dubosarsky, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Using the technology of structural, thermic, and atmogeochemical investigations a number of the studies within the Piatyhorivka area of the DnieperDonets Depression were performed. Among the studies there were the geostructural and morphostructural analyses, the structural interpretation of satellite data, field works on the emanation and thermometric surveys, laboratory chromatographic analyses of gas samples collected from the undersoil layer, integrated interpretation of atmogeochemical and remote sensing data, predicting oil-gas occurrence for the Piatyhorivka area. It is found that this area is located in the complicated structural and tectonic environment. Within its boundaries the relative "autonomic" northern and southern zones of the anomalous gas elimination are detected and five local plots of the difficult configuration in a plane projected for the further exploration of oil and gas deposits are identified.